Electroacupuncture relieves hyperalgesia by regulating neuronal–glial interaction and glutamate transporters of spinal dorsal horns in rats with acute incisional neck pain - Wang, Jun-ying; Zhang, Jin-ling; Chen, Shu-ping; Gao, Yong-hui; Zhang, Jian-liang; Chen, Yu; Zhang, Yue; Rong, Pei-jing; Liu, Jun-ling (Frontiers in Neuroscience, 2022)
Objective: Glial cells are involved in the analgesic effect of electroacupuncture (EA) in rats with chronic neurological pain. The objective of this study was to observe the role of neuronal-glial interaction and glutamate (Glu) transporters in EA-induced acute neck pain relief in rats. Materials and Methods: Male rats were placed into the following 5 groups: control, model, EA Futu (LI18), EA Hegu (LI4)-Neiguan (PC6), and EA Zusanli (ST36)-Yanglingquan (GB34). The incisional neck pain model was established by making a longitudinal incision along the midline of the neck. The thermal pain threshold (TPT) was measured using a radiation heat detector. The immunoactivities of glial fibrillary acidic protein (GFAP), ionized calcium-binding adapter molecule 1 (Iba-1), neurokinin 1 receptor (NK-1R), Glu aspartate transporter (GLAST), and Glu transporter-1 (GLT-1) in the dorsal horns of the cervico-spinal cord (C2–C5) were detected using immunofluorescence histochemistry. The expression levels of GFAP, Iba-1, GLAST, and GLT-1 mRNAs were determined using quantitative real-time polymerase chain reaction (PCR). Results: The TPT and levels of mRNAs expression and immunoactivity GLT-1 and GLAST were significantly decreased, and those of Iba-1 and GFAP were significantly increased in the model group than those of the control group (P < 0.05). The activated microgliacytes were gathered around the NK-1R positive neurons, and co-expression of NK-1R and astrocytes was observed in the model group. EA LI18 significantly increased the TPT and expression of GLAST and GLT-1 mRNAs(P < 0.05), and notably decreased the number of Iba-1 positive cells and Iba-l mRNA expression (P < 0.05), whereas GLAST and GLT-1 antagonists inhibited the analgesic effect of EA LI18. However, these effects, except for the downregulation of Iba-1 mRNA, were not observed in the EA ST36-GB34 group. Fewer NK-1R-positive neurons were visible in the spinal DHs in the EA LI18 group, and the co-expression of NK-1R and astrocytes was also lower than that in the three EA groups. Conclusion: EA of LI18 had an analgesic effect in rats with neck incisions, which may be related to it’s functions in suppressing the neuronal-glial cell interaction through NK-1R and upregulating the expression of GLAST and GLT-1 in the spinal DHs.